2022
DOI: 10.30574/gscbps.2022.20.3.0336
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and phenolic content of ginger (Zingiber officinale Roscoe) combination with cinnamon (Cinnamomum burmanii) and Sappan wood (Caesalpinia sappan) as an anti-diabetic

Abstract: Based on IDF 6.7 million people deaths due to diabetes mellitus in 2021. Current study showed that dietary of fruits and vegetables containing antioxidant have associated with the reduction of the risk of many chronic diseases such as diabetes and cardiovascular. Plant phenolic compounds can act as antioxidant individually or in combination. Zingiber officinale Roscoe, Caesalpinia sappan, and Cinnamomum burmannii have phenolic compounds. However less information about antioxidant activity of ginger in this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The analgesic and anti-inflammatory activity of a combination of Phyllanthus reticulatus and Mimosa pigra (Akhter et al, 2018). A study of the three species of Z. officinale with Cinnamomum burmannii and Caesalpinia sappan showed that the combination of ginger had either higher total phenolic or antioxidant activity than the non-combination (Mahmudati et al, 2022). Study on a combination of herbs, named Trikatuk, in many combinations, resulting in most of the combinations investigated in the present study also exhibiting additive or synergistic effects (Nutmakul & Chewchinda, 2023).…”
Section: Introductionmentioning
confidence: 52%
“…The analgesic and anti-inflammatory activity of a combination of Phyllanthus reticulatus and Mimosa pigra (Akhter et al, 2018). A study of the three species of Z. officinale with Cinnamomum burmannii and Caesalpinia sappan showed that the combination of ginger had either higher total phenolic or antioxidant activity than the non-combination (Mahmudati et al, 2022). Study on a combination of herbs, named Trikatuk, in many combinations, resulting in most of the combinations investigated in the present study also exhibiting additive or synergistic effects (Nutmakul & Chewchinda, 2023).…”
Section: Introductionmentioning
confidence: 52%